1981
DOI: 10.1128/aem.41.4.894-902.1981
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lysogeny, colicinogeny, and drug resistance in enterobacteria isolated from sewage and from rectum of humans and some domesticated species

Abstract: Enterobacteria were isolated by streaking swabs of sewage and rectal swabs from human volunteers and from domesticated animals. Thirty strains of human origin were identified as Escherichia coli. Out of 1,367 rectal isolates of animal origin, 21% were lysogenic (phi'), 29% were colicinogenic (col+), and 7% were col+ phi'. Out of 85 rectal samples more than 60% harbored variable numbers of col+ or phi' bacteria. Lysogens harboring homoimmune prophages were detectable in six out of eight human subjects in sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The taxa have varying levels of bacteriocin production that ranges from 3.4 to 26% (Table 1). This range is similar to the levels of bacteriocin production noted from prior surveys of clinical and natural strains of these same taxa (Dhillon & Dhillon, 1981; Bradley, 1991; Riley & Gordon, 1992; Smarda, 1992; Chakraborty & Nag, 1998; Gordon et al. , 1998; Murinda et al.…”
Section: Bacteriocin Production In Natural Strains Of Enteric Bacteriasupporting
confidence: 81%
See 1 more Smart Citation
“…The taxa have varying levels of bacteriocin production that ranges from 3.4 to 26% (Table 1). This range is similar to the levels of bacteriocin production noted from prior surveys of clinical and natural strains of these same taxa (Dhillon & Dhillon, 1981; Bradley, 1991; Riley & Gordon, 1992; Smarda, 1992; Chakraborty & Nag, 1998; Gordon et al. , 1998; Murinda et al.…”
Section: Bacteriocin Production In Natural Strains Of Enteric Bacteriasupporting
confidence: 81%
“…Table 2 provides a summary of how many indicator strains were killed per bacteriocin producer, as well as a pooled estimate of percentage killing per taxa for each producer. The levels of killing per taxa range from 1.5 to 6% (Dhillon & Dhillon, 1981; Bradley, 1991; Riley & Gordon, 1992; Smarda, 1992; Chakraborty & Nag, 1998; Gordon et al. , 1998; Murinda et al.…”
Section: Bacteriocin Production In Natural Strains Of Enteric Bacteriamentioning
confidence: 99%
“…Many studies of microbiological pollution of water now evaluate antibiotic resistance of isolates with a view toward public health considerations (Armstrong, et a!., 1981(Armstrong, et a!., , 1982Cooke, 1976;Dhillon and Dhillon, 1981;Grabow, et al, 1975;Niemi, et aL, 1983;Shaw and Cabelli, 1980). However, the number and kinds of antibiotics differed in each of those studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, reviews indicate somewhat ambiguous experimental results (Hardy, 1975(Hardy, , 1978. Dhillon and Dhillon (1981) found that 38 percent of enterobacteria isolated from cattle was colicinogenic and that the colicinogenicity could be transmitted with 22 percent of the isolates. We have found no other reports in the literature with respect to colicinogenicity of bovine E. coii isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Free phages in different environments can also be produced by lysogenic induction of prophages (Dhillon et al 1976; Weinbauer and Suttle 1996;Jiang and Paul 1998). Moreover many faecal bacteria including E. coli contain inducible prophages in their genome (Dhillon and Dhillon 1981;Schicklmaier et al 1998). However, for the topic of interest in this review the question is whether phages produced by induction of lysogenic strains present in the water environment have any influence on the numbers of somatic coliphages detected by E. coli strains WG5 and CN13.…”
Section: Potential Contribution Of Lysogenic Induction To the Free Phmentioning
confidence: 99%